Impact of potential fluctuation on temperature dependence of optical gain characteristics in InGaN quantum-well laser diodes. (10th November 2021) - Oshima, Itsuki; Ikeda, Yuma; Sakai, Shigeta; Yamaguchi, Atsushi A.; Kusanagi, Susumu; Kanitani, Yuya; Kudo, Yoshihiro; Tomiya, Shigetaka
Abstract: The effects of the potential fluctuation (alloy compositional fluctuation and/or well-width fluctuation) in InGaN quantum wells (QWs) on the characteristics of InGaN-QW lasers, have been theoretically investigated, and it is found that the temperature dependence of the lasing threshold is strongly affected by the degree of fluctuation. Furthermore, we have experimentally measured the temperature dependence of stimulated-emission threshold excitation power density in photo-pump measurements, and have observed the predicted behavior of temperature dependence. It is considered that the temperature dependence of the lasing threshold could be used for the evaluation of the degree of the potential fluctuation in active layers of InGaN QW lasers.